Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.tvjl.2014.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Detection of respiratory viruses and Bordetella bronchiseptica in dogs with acute respiratory tract infections

Abstract: Canine infectious respiratory disease (CIRD) is an acute, highly contagious disease complex caused by a variety of infectious agents. At present, the role of viral and bacterial components as primary or secondary pathogens in CIRD is not fully understood. The aim of this study was to investigate the prevalence of canine parainfluenza virus (CPIV), canine adenovirus type 2 (CAV-2), canine influenza virus (CIV), canine respiratory coronavirus (CRCoV), canine herpes virus-1 (CHV-1), canine distemper virus (CDV) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
98
8
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(122 citation statements)
references
References 27 publications
4
98
8
2
Order By: Relevance
“…In all animals, at least one of the infectious agents was detected, and in most cases (65%) co-infections were confirmed. These results are in contrast to those obtained in studies carried out in the UK, Japan, and Thailand, where co-infections accounted for no more than 15%, and in Germany, where they accounted for approximately 37% of animals with kennel cough symptoms (Erles et al 2004;Mochizuki et al 2008;Posuwan et al 2010;Schulz et al 2014). One of the reasons for the discrepancy between findings may be the fact that in our study co-infections were primarily caused by the combination of CHV and another pathogen, which may indicate a chronic form of the disease.…”
Section: Pathogenscontrasting
confidence: 98%
See 3 more Smart Citations
“…In all animals, at least one of the infectious agents was detected, and in most cases (65%) co-infections were confirmed. These results are in contrast to those obtained in studies carried out in the UK, Japan, and Thailand, where co-infections accounted for no more than 15%, and in Germany, where they accounted for approximately 37% of animals with kennel cough symptoms (Erles et al 2004;Mochizuki et al 2008;Posuwan et al 2010;Schulz et al 2014). One of the reasons for the discrepancy between findings may be the fact that in our study co-infections were primarily caused by the combination of CHV and another pathogen, which may indicate a chronic form of the disease.…”
Section: Pathogenscontrasting
confidence: 98%
“…In a study carried out by in India, this microorganism was only found in 2 out of 68 dogs exhibiting kennel cough symptoms. A different situation was reported in Germany, where the presence of Bordetella bronchiseptica was confirmed in as many as 78% symptomatic dogs, and in most cases it was the only isolated infectious agent (Schulz et al 2014). The results obtained in our study may indicate that this bacterium is an important aetiological factor of kennel cough, although not the most frequent one in Poland.…”
Section: Pathogenscontrasting
confidence: 59%
See 2 more Smart Citations
“…SCHULZ et al (2014) have reported that in addition to CAV-2, canine parainfluenza virus, canine influenza virus, canine respiratory coronavirus, as well as B. bronchiseptica were detected in varying rates among the shelter and the owned dogs, with or without acute respiratory system infection. Further, the presence of B. bronchiseptica was significantly higher in dogs with clinical respiratory infection than in the healthy looking dogs (45.6% and 78.7%, respectively); there was a high prevalence of multiple infections.…”
Section: Discussionmentioning
confidence: 99%